2017
DOI: 10.3389/fimmu.2017.00802
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Senescent T-Cell Phenotype Correlates with Clinical Severity in GATA Binding Protein 2-Deficient Patients

Abstract: GATA binding protein 2 (GATA2) deficiency is a rare disorder of hematopoiesis, lymphatics, and immunity caused by spontaneous or autosomal dominant mutations in the GATA2 gene. Clinical manifestations range from neutropenia, lymphedema, deafness, to severe viral and mycobacterial infections, bone marrow failure, and acute myeloid leukemia. Patients also present with monocytopenia, dendritic cell, B- and natural killer (NK)-cell deficiency. We studied the T-cell and NK-cell compartments of four GATA2-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…GATA binding protein 2 (GATA2) deficiency is a rare disorder that has clinical manifestations of bone marrow failure, acute myeloid leukemia, deafness, severe viral, and bacterial infections. In a small number of GATA2-deficient patients with history of severe infections, the expansion of memory CD8 + T-cells was reported [40]. These findings, together with the results of our study, support that CD8 + T-cell senescence can occur in patients with PIDs, especially those who have suffered from significant infections.…”
Section: Discussionsupporting
confidence: 88%
“…GATA binding protein 2 (GATA2) deficiency is a rare disorder that has clinical manifestations of bone marrow failure, acute myeloid leukemia, deafness, severe viral, and bacterial infections. In a small number of GATA2-deficient patients with history of severe infections, the expansion of memory CD8 + T-cells was reported [40]. These findings, together with the results of our study, support that CD8 + T-cell senescence can occur in patients with PIDs, especially those who have suffered from significant infections.…”
Section: Discussionsupporting
confidence: 88%
“…The remaining NK cells have decreased CXCL12/CXCR4-dependent chemotaxis, while the B cells have increased CXCL12-induced chemotaxis 48 . Ruiz-Garcia studied four patients and showed that those with worse clinical phenotype had increased T cell senescence 49 .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…GATA2 deficient patients showed severe immunological features in parallel with senescent T cell phenotype and B cell lymphopenia. This gene is also reported more frequently in CVID pre-diagnosed patients in Mediterranean region populations 27 , 28 .…”
Section: Methodsmentioning
confidence: 69%